The effect of milk consumption with different temperatures after resistance exercise on appetite and energy intake in active girls: A pilot study - Naghoni Bahar Karimi; Kęska Anna; Ebrahimi Mohsen (Biomedical Human Kinetics)
Study aim: The aim of this study was to investigate the effect of milk consumption with different temperatures after resistance training on appetite and energy intake (EI) in active girls.